Mitigation of starch-induced postprandial glycemic spikes in rats by antioxidants-rich extract of Cicer arietinum Linn. seeds and sprouts - Ashok Kumar Tiwari; Chinthapatla Sahana; Amtul Zehra; Kuncha Madhusudana; Domati Anand Kumar; Sachin Bharat Agawane (Wolters Kluwer Medknow Publications, 2013)
Introduction: Consumption of highly processed calories dense diet leads abrupt increase in postprandial blood glucose level, which in turn induces immediate oxidative stress. Postprandial hyperglycemia (PPHG) and resultant oxidative stress is one of the earliest detectable abnormalities in diabetes prone individuals, independent risk factor for development of cardiovascular disorders (CVD), a major pathophysiological link between diabetes and CVD and an important contributing factor in atherogenesis even in non-diabetic individuals. Therefore, dietary supplements mitigating PPHG spikes along with potent antioxidant activities may help decrease development of PPHG and oxidative stress induced pathogenesis. Objectives: The study evaluated free radicals scavenging, antioxidant properties and intestinal α-glucosidase inhibitory activity in methanol extract of two varieties of Cicer arietinum Linn viz. Bengal gram and Kabuli chana and green gram (Vigna radiata Linn. Wilczek) raw grains and their sprouts and studied their influence on starch-induced postprandial glycemic excursion in rats. Materials and Methods: Healthy grains were procured from local markets. Free radicals scavenging antioxidant and glucose-induced hemoglobin (Hb)-glycation inhibition activities were analyzed using standard in vitro procedures. In vitro antihyperglycemic activity was evaluated by assessing rat intestinal α-glucosidase inhibitory activity. Influence on starch-induced postprandial glycemic excursion in rats was studied by pre-treatment of rats with extracts. Results: Compared with raw seeds increase in total polyphenol and flavonoids concentration in green gram sprouts and Kabuli chana sprouts (KCs) were observed. Total protein concentrations in sprouts did not differ from non-sprouted grains. 2,2'- Azinobis (3-ethyl benzthiazoline-6-sulphonic acid) cation scavenging activity was more than twice in Bengal gram sprouts of (BGs) and KCs than their raw seeds. 2,2-diphenyl-1-picrylhydrazyl, hydrogen peroxide scavenging, nitro blue tetrazolium reducing and glucose-induced Hb-glycation inhibitory activity did not differ from non-sprouted raw grains. Increase in rat intestinal α-glucosidase inhibitory activity was observed in BGs and KCs. BGs significantly mitigated 1 st 30 min starch-induced postprandial glycemic excursions and reduced 2 h postprandial glycemic load. Conclusion: Sprouting leads dynamic changes in free radicals scavenging potentials and antioxidant activities in grains. Consumption of seeds as well as BGs before the starch-rich meal can significantly mitigate 1 st 30 min postprandial glycemic excursion and reduce 2 h postprandial glycemic burden.